2017
DOI: 10.1016/j.eml.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Transversal–rotational and zero group velocity modes in tunable magneto-granular phononic crystals

Abstract: We report on the design and operation of a 1D magneto-granular phononic crystal composed of a chain of steel spherical beads on top of permanent magnets. The magnetic field of the permanent magnets induces forces in the granular structure. By changing its strength, we can tune the dynamic response of the granular structure. We present experimental results with evidence of coupled transversal-rotational modes, and zero group velocities modes. These observations are well supported by a proposed model taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Granular crystals, as these systems became known, can be considered a class of phononic crystal [4] with unique behavior specific to granular media. For instance, in addition to nonlinear effects such as solitons and discrete breathers [2,3], unusual linear phenomena such as the existence of rotational acoustic modes have been revealed [5,6]. Due to the nonlinearity of Hertzian contacts, the acoustic properties of granular crystals can be easily tuned, for example, by applying static compression, which makes them attractive for potential applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Granular crystals, as these systems became known, can be considered a class of phononic crystal [4] with unique behavior specific to granular media. For instance, in addition to nonlinear effects such as solitons and discrete breathers [2,3], unusual linear phenomena such as the existence of rotational acoustic modes have been revealed [5,6]. Due to the nonlinearity of Hertzian contacts, the acoustic properties of granular crystals can be easily tuned, for example, by applying static compression, which makes them attractive for potential applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Review on the topic has been prepared by Hadjesfandiari and Dargush [38], which concluded that when an elastic wave propagates through the medium considered in accordance with generalized elasticity concepts, its elements undergo angular motions. Despite the fact that the micromorphic approach is more visible in acoustics or in the studies on various materials than in the geophysics, recent [39][40][41] search for laboratory confirmation of the micromorphic concepts of seismic rotation yielded sound results, as well.…”
Section: Seismic Rotation In Various Continuum Modelsmentioning
confidence: 99%
“…The tunability of contact mechanics via external precompression has been explored at the mesoscale for multiple engineering applications, e.g., filters [15][16][17], acoustic lenses [18], and rectifiers [19]. More recently, external magnetic fields have been used to control the dynamics of ferromagnetic beads for the realization of one-dimensional tunable magnetogranular chains, where the interparticle contact forces are varied by changing the applied field [20,21]. The prospect of achieving tunability by using external, noncontact interaction forces is also particularly appealing in the context of SAWs, where examples of tunable systems are still limited [22,23] with respect to bulk and plate structures [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%